Zero-Energy Cool Chamber in Anthracnose Disease Management of Postharvest Capsicum frutescens - Filaila, Nuzila Fitri; Suryanti, Suryanti; Widiastuti, Ani (Jurnal Fitopatologi Indonesia, 2021)
Anthracnose caused by Colletotrichum gloeosporioides is one of important diseases causing postharvest losses on chili. This study aimed to determine the effectiveness of the zero energy cool chamber (ZECC) in reducing the severity of anthracnose in Capsicum frutescens L. and extending the shelf life of chilies. The research was started by designing and building ZECC as a storage area for chilies. Chilies with and without fungal inoculation were stored in ZECC and storage chamber at room temperature. C. gloeosporioides experienced a growth inhibition of 40.48% after being stored in ZECC compared to its growth at room temperature. Storage of chilies in ZECC was able to reduce the severity of anthracnose by 56.2% on the 15th day, did not affect vitamin C content and total dissolved solids (TSS) and was able to reduce chilies weight loss during storage. Based on the organovisual test using the visual quality rating method and the Hedonic sensory test, consumers prefer chilies stored in the ZECC. The results showed that storage in ZECC could extend the shelf life of chilies. This storage model does not use electricity or is zero energy so it can be used by small scale farmers. This is the first report on the use of ZECC for the management of anthracnose in postharvest chilies in Indonesia.